POLA TANAM DALAM DUSUNG DI NEGERI KAMARIAN KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Salombe, Resky; Wattimena, Cornelia M. A.; Talaohu, Moda (MARSEGU : Jurnal Sains dan Teknologi, 2025)
Dusung is a traditional agroforestry system of the Maluku people, inherited across generations as an ecological, economic, and cultural strategy for land management. This study aims to identify the plant combinations and cropping patterns applied by the community in Kamarian Village, Kairatu Subdistrict, West Seram Regency. The research employed a descriptive approach using qualitative and quantitative techniques through observation, interviews, and documentation involving ten dusung owners selected by purposive sampling. The results show two main patterns in the dusung system, namely Tree Along Border (TAB) and Mixture Random. The TAB pattern is characterized by planting forestry species such as Alstonia scholaris, Erythrina variegata, and Gliricidia sepium along the field edges as natural fences, while the central area is filled with plantation and fruit crops such as nutmeg, clove, coconut, durian, langsat, and mango. Meanwhile, the Mixture Random pattern features irregular planting with higher species diversity, including food crops such as sago, banana, pineapple, and cassava. The choice of plant combinations is influenced by economic value, ecological suitability, socio-cultural significance, and local seed availability. Overall, the dusung system plays an essential role in maintaining ecosystem balance, improving household livelihoods, and preserving the cultural identity of the Kamarian community.